Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan Ppkn Menggunakan Model Ragam - Desy Winda Sari; Noorhapizah (CV. ITTC INDONESIA, 2025)
The reason for this study is to depict the improvement in the nature of educator exercises, understudy learning exercises, and understudy learning results. in the wake of learning is completed utilizing the RAGAM learning model. This sort of examination utilizes Study hall Activity Exploration (Vehicle). The subjects of this review were 4th grade understudies at SDN Kuin Cerucuk 4 Banjarmasin. The sort of information in this review is quantitative information acquired through composed tests, and subjective information got through noticing educator exercises and understudy exercises. This exploration occurred in 4 gatherings, the outcomes showed that educator action arrived at a score of 28 with excellent standards. Perception of understudy movement arrived at a level of 90% with extremely dynamic standards. Mental learning results arrive at 91% In light of this examination, the RAGAM model can increment educator movement, understudy action, and learning results.